Validation of the easy‐to‐use lenvatinib prognostic index to predict prognosis in advanced hepatocellular carcinoma patients treated with lenvatinib. Issue 12 (25th August 2022) - Rimini, Margherita; Kang, Wonseok; Burgio, Valentina; Persano, Mara; Aoki, Tamoko; Shimose, Shigeo; Tada, Toshifumi; Kumada, Takashi; Sho, Takuya; Lai, Eleonora; Celsa, Ciro; Campani, Claudia; et al.
Abstract: Aim: The identification of new prognostic factors able to stratify hepatocellular carcinoma patients candidate to first‐line therapy is urgent. In the present work we validated the prognostic value of the lenvatinib prognostic index. Methods: Data of Eastern and Western patients treated with lenvatinib as first‐line for Barcelona Clinic Liver Cancer stage B or C hepatocellular carcinoma were recollected. The lenvatinib prognostic index was composed by three classes of risk according with our previous study. The "low risk" group includes patients with prognostic nutritional index (PNI) >43.3 and with previous transarterial chemoembolization. The "medium risk" group includes patients with PNI >43.3, but without previous transarterial chemoembolization and patients with PNI <43.3, albumin‐bilirubin grade 1 and Barcelona Clinic Liver Cancer stage B. The "high risk" group includes patients with PNI <43.3, albumin‐bilirubin grade 2, and patients with PNI <43.3, albumin‐bilirubin grade 1 and Barcelona Clinic Liver Cancer stage C. Results: A total of 717 patients were included. The median overall survival was 20.7 months (95% CI 16.1–51.6) in patients with low risk ( n = 223), 16.7 months (95% CI 13.3–47.0) in patients with medium risk ( n = 264), and 10.7 months (95% CI 9.3–12.2) in patients with high risk ( n = 230; HR 1, 1.29, and 1.92, respectively; p < 0.0001). Median progression‐free survival was 7.3 months (95% CI 6.3–46.5) in patients with low risk, 6.4 months (95% CI 5.3–8.0) in patients with medium risk, and 4.9 months (95% CI 4.3–5.5) in patients with high risk (HR 1, 1.07, 1.47 respectively; p = 0.0009). Conclusion: The lenvatinib prognostic index confirms its prognostic value on an external cohort of hepatocellular carcinoma patients treated with Lenvatinib.